2021
DOI: 10.1016/j.scitotenv.2020.143921
|View full text |Cite
|
Sign up to set email alerts
|

One-year measurements of secondary organic aerosol (SOA) markers in the Paris region (France): Concentrations, gas/particle partitioning and SOA source apportionment

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 149 publications
(208 reference statements)
3
42
0
Order By: Relevance
“…chemical mass balance (CMB) and positive matrix factorization (PMF)) (Watson et al, 1990;Paatero, 1997;Paatero and Tapper, 1994), SOA-tracer method (Kleindienst et al, 2007) and radiocarbon ( 14 C) measurements (Szidat et al, 2009;Gelencsér et al, 2007). These methodologies have been successfully applied worldwide and, in general, good agreements have been reported when compared by twos directly (Song et al, 2006;Kim et al, 2004;Kleindienst et al, 2010;Pachon et al, 2010;Heo et al, 2013;Al-Naiema et al, 2018;Srivastava et al, 2018b;Bove et al, 2018;Bae et al, 2019;Antony Chen and Cao, 2018;Hettiyadura et al, 2018;Jiang et al, 2018;Keerthi et al, 2018;Matawle et al, 2018;Shi et al, 2018;Shirmohammadi et al, 2016;Lanzafame et al, 2020). However, large discrepancies have been also observed when apportioning the SOA fraction, depending on the methods compared, the period of the year considered or atmospheric conditions observed (Srivastava et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…chemical mass balance (CMB) and positive matrix factorization (PMF)) (Watson et al, 1990;Paatero, 1997;Paatero and Tapper, 1994), SOA-tracer method (Kleindienst et al, 2007) and radiocarbon ( 14 C) measurements (Szidat et al, 2009;Gelencsér et al, 2007). These methodologies have been successfully applied worldwide and, in general, good agreements have been reported when compared by twos directly (Song et al, 2006;Kim et al, 2004;Kleindienst et al, 2010;Pachon et al, 2010;Heo et al, 2013;Al-Naiema et al, 2018;Srivastava et al, 2018b;Bove et al, 2018;Bae et al, 2019;Antony Chen and Cao, 2018;Hettiyadura et al, 2018;Jiang et al, 2018;Keerthi et al, 2018;Matawle et al, 2018;Shi et al, 2018;Shirmohammadi et al, 2016;Lanzafame et al, 2020). However, large discrepancies have been also observed when apportioning the SOA fraction, depending on the methods compared, the period of the year considered or atmospheric conditions observed (Srivastava et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the chemical profile is also quite variable. Indeed, this PMF factor is not well described in the literature, and few studies reported it so far (Srivastava et al, 2019;Lanzafame et al, 2020;Borlaza et al, 2020). As a result, we do not know for instance the loading of HULIS, quinone or isoprene-derived-compounds contained in this factor, nor the amount of ageing it presents at each site.…”
Section: Secondary Organics Aerosolsmentioning
confidence: 92%
“…Recently, some of these SOA markers could be monitored offline at a couple of sites within the CARA program (i.e., Grenoble and SIRTA). Their use in PMF analysis allowed the deconvolution and apportionment of different SOA sources not commonly resolved in the literature, highlighting substantial contributions of specific biogenic and anthropogenic SOA factors [18], [20], [21], [117]. More precisely, a peculiar secondary anthropogenic fraction could be evidenced in Grenoble, possibly related with Fenton-like chemistry and self-amplification cycle of SOA formation during wintertime PM pollution episodes [18].…”
Section: Secondary Organic Aerosols (Soa)mentioning
confidence: 99%
“…At SIRTA, various anthropogenic SOA fractions could be linked to different secondary oxidation processes involving the following precursors: toluene and naphthalene, phenolic compounds, and PAHs (notably leading to the formation of DHOPA and phthalic acid, methylnitrocatechols and oxy/nitro-PAHs, respectively). These precursors are assumed to be mainly emitted by biomass burning and vehicular exhaust, and the sum of corresponding SOA loadings might represent up to 40% of daily PM10 concentrations in Greater Paris during the winter season [21], [117].…”
Section: Secondary Organic Aerosols (Soa)mentioning
confidence: 99%
See 1 more Smart Citation